IDNLearn.com: Your one-stop destination for finding reliable answers. Ask anything and get well-informed, reliable answers from our knowledgeable community members.
Sagot :
To find the pair of points representing the solution set of the system of equations:
1. First, we have the equations:
[tex]\[ y = x^2 - 2x - 19 \][/tex]
[tex]\[ y + 4x = 5 \][/tex]
2. We substitute the expression for [tex]\(y\)[/tex] from the second equation into the first equation. From the second equation, solve for [tex]\(y\)[/tex]:
[tex]\[ y = 5 - 4x \][/tex]
3. Substitute [tex]\( y = 5 - 4x \)[/tex] into the first equation:
[tex]\[ 5 - 4x = x^2 - 2x - 19 \][/tex]
4. Rearrange the equation to form a standard quadratic equation:
[tex]\[ x^2 - 2x - 19 - 5 + 4x = 0 \][/tex]
[tex]\[ x^2 + 2x - 24 = 0 \][/tex]
5. Factorize or use the quadratic formula to solve for [tex]\(x\)[/tex]. The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( c = -24 \)[/tex].
[tex]\[ x = \frac{-2 \pm \sqrt{2^2 - 4(1)(-24)}}{2(1)} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{4 + 96}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{100}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm 10}{2} \][/tex]
This gives us two solutions for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{8}{2} = 4 \][/tex]
[tex]\[ x = \frac{-12}{2} = -6 \][/tex]
6. Substitute these [tex]\(x\)[/tex]-values back into the second equation to find the corresponding [tex]\(y\)[/tex]-values:
For [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 5 - 4(4) = 5 - 16 = -11 \][/tex]
For [tex]\( x = -6 \)[/tex]:
[tex]\[ y = 5 - 4(-6) = 5 + 24 = 29 \][/tex]
The pair of points representing the solutions to the system of equations are [tex]\((-6, 29)\)[/tex] and [tex]\((4, -11)\)[/tex].
Therefore, the missing pair of points is:
[tex]\[ (4, -11) \][/tex]
1. First, we have the equations:
[tex]\[ y = x^2 - 2x - 19 \][/tex]
[tex]\[ y + 4x = 5 \][/tex]
2. We substitute the expression for [tex]\(y\)[/tex] from the second equation into the first equation. From the second equation, solve for [tex]\(y\)[/tex]:
[tex]\[ y = 5 - 4x \][/tex]
3. Substitute [tex]\( y = 5 - 4x \)[/tex] into the first equation:
[tex]\[ 5 - 4x = x^2 - 2x - 19 \][/tex]
4. Rearrange the equation to form a standard quadratic equation:
[tex]\[ x^2 - 2x - 19 - 5 + 4x = 0 \][/tex]
[tex]\[ x^2 + 2x - 24 = 0 \][/tex]
5. Factorize or use the quadratic formula to solve for [tex]\(x\)[/tex]. The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( c = -24 \)[/tex].
[tex]\[ x = \frac{-2 \pm \sqrt{2^2 - 4(1)(-24)}}{2(1)} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{4 + 96}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{100}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm 10}{2} \][/tex]
This gives us two solutions for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{8}{2} = 4 \][/tex]
[tex]\[ x = \frac{-12}{2} = -6 \][/tex]
6. Substitute these [tex]\(x\)[/tex]-values back into the second equation to find the corresponding [tex]\(y\)[/tex]-values:
For [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 5 - 4(4) = 5 - 16 = -11 \][/tex]
For [tex]\( x = -6 \)[/tex]:
[tex]\[ y = 5 - 4(-6) = 5 + 24 = 29 \][/tex]
The pair of points representing the solutions to the system of equations are [tex]\((-6, 29)\)[/tex] and [tex]\((4, -11)\)[/tex].
Therefore, the missing pair of points is:
[tex]\[ (4, -11) \][/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Your questions are important to us at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.